2014
DOI: 10.1038/aps.2013.182
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α induces CXCL1 chemokine expression and release in human vascular endothelial cells in vitro via two distinct signaling pathways

Abstract: TNF-α stimulates CXCL1 release from human ECs through JNK-mediated CXCL1 mRNA expression and p38 MAPK- and PI-3K-mediated CXCL1 secretory processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 30 publications
4
53
1
Order By: Relevance
“…6b), suggesting that lack of presenilins affects TNF␣-mediated CXCL1 chemokine production. Interestingly, and consistent with our reported defect in JNK MAPK activation in PS DKO MEFs, it has been reported that CXCL1 production is dependent upon TNF␣-stimulated JNK MAPK activation (72)(73)(74). To further validate this observation, we used wild type and the partial knock-out Psen1 ϩ/Ϫ / Psen2 Ϫ/Ϫ murine model, which have the maximum reduction in presenilin expression that is compatible with viability.…”
Section: Presenilin Deficiency Is Associated With Enhanced Formation supporting
confidence: 77%
“…6b), suggesting that lack of presenilins affects TNF␣-mediated CXCL1 chemokine production. Interestingly, and consistent with our reported defect in JNK MAPK activation in PS DKO MEFs, it has been reported that CXCL1 production is dependent upon TNF␣-stimulated JNK MAPK activation (72)(73)(74). To further validate this observation, we used wild type and the partial knock-out Psen1 ϩ/Ϫ / Psen2 Ϫ/Ϫ murine model, which have the maximum reduction in presenilin expression that is compatible with viability.…”
Section: Presenilin Deficiency Is Associated With Enhanced Formation supporting
confidence: 77%
“…4A and B. We observed that SB202190 did not affect p38 MAPK phosphorylation, even though its specificity and inhibitory ability on p38 MAPK have been demonstrated by us and others [23,24]. Under these conditions, we observed that both JNK and p38 MAPK inhibitors markedly inhibited TNF-α-induced Akt activation and slightly affected PI-3K activation.…”
Section: Resultssupporting
confidence: 62%
“…3). In this regard, the regulatory mechanism by TNF-α in A549 cells is similar to that observed in human umbilical vein endothelial cells (HUVECs) treated with TNF-α [24]. However, there are also some differences between these two cell types in response to TNF-α and other stimulators, revealing an interesting cell type-specific feature.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The ECs were prepared and characterized by a previously described method. 23,24 Isolated ECs were maintained in M199 containing 20% fetal bovine serum, 30 µg/mL endothelial cell growth supplement, 4 mM L-glutamine, 100 U/mL penicillin, 100 µg/mL streptomycin, and 250 ng/mL Fungizone (Thermo Fisher Scientific). The cells were used between the second and fourth passages in this study.…”
Section: Cell Culturesmentioning
confidence: 99%